Bibliometric Analysis of Electric Vehicle Adoption and Environmental Sustainability Research (2014?2024): Trends and Implications - Hassan A.; Mahmoud M.A.; Al-Sharafi M.A.; Ibrahim M.; Iahad N.A.; Gunasekaran S.S. (Springer Science and Business Media Deutschland GmbH, 2025)
Electric vehicles (EVs) offer major sustainability benefits through reductions in greenhouse gas emissions and noise pollution. This study presents a bibliometric analysis of the literature on EV adoption and environmental sustainability from 2014 to 2024. The aim is to uncover publication trends, influential countries, research themes, gaps, and future directions. A systematic search of Scopus yielded 121 documents for analysis using VOSviewer. Results reveal an upward trajectory in publications, signaling intensifying research attention, especially post-2019. The US and China dominate research outputs. However, developing countries are underrepresented, indicating a contextual knowledge gap. Analysis of keywords and citations shows emphasis on environmental impacts, consumer attitudes, charging infrastructure, incentives, costs, and policy. Key themes represent research priorities for scholars and stakeholders. Multi-country collaborations and studies grounded in developing world contexts can enrich the discourse. Interdisciplinary perspectives embracing technical, social, economic and policy dimensions are valuable. The study provides a foundation to advance research and evidence-based policies for accelerated EV adoption globally through targeted strategies addressing region-specific barriers. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.